2019
DOI: 10.1159/000496460
|View full text |Cite
|
Sign up to set email alerts
|

Low Skeletal Muscle Mass Independently Predicts Mortality in Patients with Chronic Heart Failure after an Acute Hospitalization

Abstract: Background: Heart failure (HF) is a syndrome associated with exercise intolerance, and its symptoms are more common in patients with low skeletal muscle mass (SMM). Estimation of muscle mass can be cumbersome and unreliable, particularly in patients with varying body weight. The psoas muscle area (PMA) can be used as a surrogate of sarcopenia and has been associated with poor outcomes in other populations. Objectives: The aim of this study was to assess if sarcopenia is associated with the survival of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 38 publications
0
32
0
5
Order By: Relevance
“…24 Previous studies have aimed to use skeletal muscle mass as a predictor of death in patients with HF but were hampered by methodological problems, sample size, or both. For example, Lopez et al 6 have tried to extrapolate skeletal muscle mass using abdominopelvic computed tomography scans performed during an acute hospitalization in order to diagnose sarcopenia in 160 patients with HF, and they observed a 4.5-fold increase in the risk of death in those patients labelled as sarcopenic. However, it is difficult, if not impossible, to use abdominopelvic imaging to understand appendicular skeletal muscle mass.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 Previous studies have aimed to use skeletal muscle mass as a predictor of death in patients with HF but were hampered by methodological problems, sample size, or both. For example, Lopez et al 6 have tried to extrapolate skeletal muscle mass using abdominopelvic computed tomography scans performed during an acute hospitalization in order to diagnose sarcopenia in 160 patients with HF, and they observed a 4.5-fold increase in the risk of death in those patients labelled as sarcopenic. However, it is difficult, if not impossible, to use abdominopelvic imaging to understand appendicular skeletal muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…The large range mirrors the association with the cohort under investigation. For example, stable ambulatory patients seem to have lower prevalence values than patients with acute or advanced HF, [5][6][7] and patients with dilated cardiomyopathy may have higher prevalence values than patients with ischaemic heart disease. 2,3,8 It is important to note that skeletal muscle wasting, in geriatric populations commonly called sarcopenia, is different from cachexia, because only cachexia is by definition associated with weight loss.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 In the present study, quadriceps muscle strength was reduced in the nondominant limb in subjects with inspiratory muscle weakness and with no significant influence on the 6-min walk test distance. The lower limbs, such as the quadriceps and psoas muscles, 28 have antigravitational postural activity, and they may be affected first during inactivity, rather than the upper limbs. 29 In the upper limbs, we observed similar handgrip strength in the inspiratory muscle weakness and the no inspiratory muscle weakness groups, probably because our subjects had mild-to-moderate chronic heart failure (New York Heart Association functional class II and III), without a global myopathy.…”
Section: Discussionmentioning
confidence: 99%
“…In CV disease, the importance and high prevalence of reduced muscle mass have only recently been recognized and can be much higher than in healthy elderly subjects ( Table 3 ). 37,70–81 Tsuchida et al 71 . have shown that the prevalence of muscle wasting is 52.6% among patients with decompensated acute HF with a mean age 64 years.…”
Section: Sarcopenia/muscle Wasting and Cardiovascular Diseases In CLImentioning
confidence: 99%